2016
DOI: 10.1055/s-0036-1586754
|View full text |Cite
|
Sign up to set email alerts
|

Management of Supplemental Oxygen for Infants with Persistent Pulmonary Hypertension of Newborn: A Survey

Abstract: Objective To evaluate practice variations amongst neonatologists regarding oxygen management in neonates with persistent pulmonary hypertension of newborn (PPHN). Study Design An online survey was administered to neonatologists to assess goal oxygenation targets and oxygen titration practices in PPHN. Response variations were assessed and intergroup comparisons performed. Results Thirty-three percent (492) of neonatologists completed the survey. Twenty-eight percent reported using specific oxygen titration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…In line with this, we found longer time periods of SpO 2 > 98% compared to SpO 2 < 92% within this study, indicating that the neonatologists were attentive in preventing hypoxemia but were permissive of hyperoxemia. These findings are consistent with a previous survey among 492 neonatologists in the USA that evaluated oxygen management in infants with PPHN [ 23 ]. The survey demonstrated that a significant number of neonatologists preferred to target higher SpO 2 and/or PaO 2 to avoid hypoxemia but did not use an upper limit of SpO 2 and PaO 2 to prevent hyperoxemia.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In line with this, we found longer time periods of SpO 2 > 98% compared to SpO 2 < 92% within this study, indicating that the neonatologists were attentive in preventing hypoxemia but were permissive of hyperoxemia. These findings are consistent with a previous survey among 492 neonatologists in the USA that evaluated oxygen management in infants with PPHN [ 23 ]. The survey demonstrated that a significant number of neonatologists preferred to target higher SpO 2 and/or PaO 2 to avoid hypoxemia but did not use an upper limit of SpO 2 and PaO 2 to prevent hyperoxemia.…”
Section: Discussionsupporting
confidence: 92%
“…The survey demonstrated that a significant number of neonatologists preferred to target higher SpO 2 and/or PaO 2 to avoid hypoxemia but did not use an upper limit of SpO 2 and PaO 2 to prevent hyperoxemia. Furthermore, a small but notable portion of neonatologists (6%) opted to administer 100% oxygen, irrespective of the oxygenation parameters, until they were confident that the infant had clinically stabilized [ 23 ]. The permissive attitude towards hyperoxemia is also reflected by the current significant variations in practice with respect to oxygen titration strategies and the lack of evidence-based guidelines for oxygen weaning in the management of PPHN [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey of neonatologist (492/1500 or 33% response rate) working in level 3 or 4 neonatal intensive care units (NICUs) across the USA evaluating oxygen management in neonates with PPHN has shown wide practice variations regarding the optimal oxyhemoglobin saturation or oxygen tension targets [ 58 ]. Seventy percent (70%) of respondents chose capillary SO 2 targets > 95%, and 11% aimed to achieve arterial PO 2 > 120 mm Hg, while as many as 6% preferred to treat with 100% oxygen until they were confident that the pulmonary vascular reactivity had stabilized and did not wean FIO 2 despite SO 2 of 100%.…”
Section: Oxygen Use For Pphn In the Neonatal Intensive Care Unit (mentioning
confidence: 99%
“…The survey responses of Nakwan et al showed similar target values [7]. However, Alapati et al in their US based survey noted that two-third of their respondents used higher saturation target > 95% and almost half targeted PaO2 > 80 mmHg, thus indicating wide variability in protocols for oxygen titration across the world [13].…”
Section: Discussionmentioning
confidence: 97%